Colonización de sustratos artificiales y naturales por hongos acuáticos zoospóricos - Marano, Agostina Virginia (2006)
We study the «in situ» colonization of different kinds of substrata by zoosporic fungi (S.D Mastigomycotina), making weekly samplings during a month in the streams «El Zanjón» and «Las Cañas» (Ensenada, Bs. As., Argentina). In those sites we put twelve different substrata, both naturals (monocotyledon leaves, crustacean shells, Rosa sp. fruits, snake sheds and little fishes) and artificial ones (cellophane fragments, polypropylene bags, slides, and two kinds of different plastic materials). The substrata were put separately in drilled plastic bags, and left for a week to allow colonization. In both sites, we observed that Saprolegnia colonized every kind of substratum (both natural and artificial ones), while Achlya was encountered in the majority of them (little fishes, slides, cellophane fragments, pieces of X-rays, Rosa sp. fruits, and monocotyledon leaves), Dichtyuchus was observed in fishes and Rosa sp. fruits, Brevilegnia and Pythium in pieces of X-rays plate and Aphanomyces only in plastic materials. Based on these preliminary results, we can infer that there is an apparent selection of some genera for particular substrata. It’s interesting to emphasize that colonization of artificial substrata by Saprolegnia, Achlya, Brevilegnia, Pythium and Aphanomyces, might suggest the possibility of using these genera in superficial biodegradation of plastic materials.